2019
DOI: 10.22438/jeb/40/2/mrn-854
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacterial endospore with longer shelf-life in improved retting of jute

Abstract: Aim :Methodology : Results:Interpretation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These three strains of Bacillus pumilus were later identified as Bacillus safensis, Bacillus velezensis and Bacillus altitudinis through whole genome sequencing based taxonomic affiliation of the isolates (Datta et al, 2020). The endospores of microbial consortium showed higher resistance to temperature, pH, UV irradiation and antibiotics than their vegetative forms and 18-month-old endospores can ret jute within 10 days with very good quality fibre (Chattopadhyay et al, 2019). Further, the immobilized strain of PJRB1 was found to have 132.6% higher xylanase production capacity over free cells after 72 hrs of incubation indicating scope of its industrial application for extra cellular xylanase production without any cellulase activity (Kundu and Majumdar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These three strains of Bacillus pumilus were later identified as Bacillus safensis, Bacillus velezensis and Bacillus altitudinis through whole genome sequencing based taxonomic affiliation of the isolates (Datta et al, 2020). The endospores of microbial consortium showed higher resistance to temperature, pH, UV irradiation and antibiotics than their vegetative forms and 18-month-old endospores can ret jute within 10 days with very good quality fibre (Chattopadhyay et al, 2019). Further, the immobilized strain of PJRB1 was found to have 132.6% higher xylanase production capacity over free cells after 72 hrs of incubation indicating scope of its industrial application for extra cellular xylanase production without any cellulase activity (Kundu and Majumdar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…High colony forming unit and higher release of pectinolytic and xylanolytic enzymes during retting of jute by 18 months old endospores resulted in completion of jute retting in 10 days with better quality jute fibre (Fibre strength of 27.6 g/tex and fibre finess of 2.51 tex) as compared to the fibre (Fibre strength of 21.8 g/tex and fibre finess of 2.84 tex) obtained by using talc based formulation. Thus the endospores of Bacillus strains can be used in place of talc based microbial formulation for higher shelf life of the product, faster retting and better fibre quality of jute (Chattopadhyay et al 2019).…”
Section: Molecular Approachmentioning
confidence: 99%
“…A microbial consortium consisting of three novel pectinolytic bacterial strains was isolated from jute retting water; this microbial consortium has very high levels of polygalacturonase (PG), pectin lyase (PNL) and xylanase activities without any cellulase activity and was found to be very useful for retting jute and mesta [ 10 ]. Retting with CRIJAF SONA has been demonstrated under farmers’ field conditions across the jute and mesta growing states of India and found to be very useful for quick retting with quality fibre production [ 11 , 12 ]. The genome sequencing of the constituent bacteria (three species of Bacillus ) revealed that the genome sizes of those bacterial strains are ∼ 3.8 Mb, with 3729 to 4002 protein-coding genes.…”
Section: Introductionmentioning
confidence: 99%